Peranan Pejabat Pembuat Akta Tanah dalam Pelaksanaan Transformasi Digital Layanan Pertanahan melalui Sertipikat Tanah Elektronik - Auliani, Intan Rifka; Roisah, Kholis (Legal Standing : Jurnal Ilmu Hukum, 2025)
This study aims to examine the readiness and obstacles to the implementation of digital transformation of land services through electronic land certificates in Indonesia, especially related to the role and authority of PPATs towards this policy. This study uses a normative juridical approach, namely a research study based on statutory regulations. The data source used is secondary data. The results show that PPATs have a role in maintaining the validity and security of land transactions through the making of valid land deeds. The existence of electronic land certificates is an effort to resolve land disputes and assist the role of the PPAT in facilitating the digitization process of land administration services such as helping to improve data security, transparency and validity, and reduce duplication or forgery of land certificates. However, there are several challenges in its implementation, such as the readiness of technological infrastructure, data security, and limited human resources skilled in information technology. By understanding the role and challenges faced by PPATs, this study provides recommendations for improving the process of issuing electronic land certificates and supporting the government's efforts to improve more modern and efficient land services in Indonesia.